Обмани меня нежно: роман / Н. В. Андреева - Андреева Наталья Вячеславовна (Детектив-загадка, 2011)
Экземпляры: Нефтебазинская библиотека (20140908) / Инвентарный номер: 234 / Цена: / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: А 65 / ББК: 84(2Рос=Рус)6